Online consumer review dan green brand experience: Faktor pendorong green repurchase intention - Asan, Sucipto (Universitas Kristen Maranatha, 2024)
Green products are often perceived as healthier, of higher quality, and as contributors to sustainable development. Accelerating green purchasing behavior is anticipated to enhance sustainability and improve quality of life. Understanding the predictive and mediating factors that influence the intention to repurchase green products is essential for expanding the green market and addressing environmental challenges. This study aims to identify these factors and assess their impact on green repurchase intention. Data were collected from 262 respondents who use green personal care products in Indonesia, employing a non-probability purposive sampling technique. The analysis was conducted using the partial least squares structural equation modeling (PLS-SEM) approach. The findings reveal that online customer reviews significantly and positively influence both green brand experience and green repurchase intention. Additionally, green brand experience was found to partially mediate the relationship between online customer reviews and green repurchase intention. This research is the first attempt to examine the link between online customer reviews and green brand experience, offering valuable insights for green brands seeking to boost repurchase rates. Companies are advised to enhance customers' green brand experiences by encouraging authentic customer reviews that emphasize the green aspects of the brand, thereby reinforcing the brand's green image and driving repeat purchases.